2020
DOI: 10.1080/09585192.2020.1811368
|View full text |Cite
|
Sign up to set email alerts
|

The unique and common effects of emotional intelligence dimensions on job satisfaction and facets of job performance: an exploratory study in three countries

Abstract: Previous empirical studies have either used a unidimensional or a multidimensional analytical approach to examine the consequences of emotional intelligence (EI). In this exploratory study we integrate and extend these two approaches, using a novel perspective to better understand the structure of the EIjob satisfaction and the EI-job performance relationship. Using commonality analysis and data from Germany, India, as well as the U.S. we partition the explained variance for job satisfaction, in-role performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 90 publications
(113 reference statements)
0
11
0
Order By: Relevance
“…In this case, job satisfaction becomes an important factor to consider in an effort to improve employee performance. Job satisfaction is a powerful motivator that can influence the relationship between emotional intelligence and performance (Chin and Yusof, 2017; Schlaegel et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, job satisfaction becomes an important factor to consider in an effort to improve employee performance. Job satisfaction is a powerful motivator that can influence the relationship between emotional intelligence and performance (Chin and Yusof, 2017; Schlaegel et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, job satisfaction becomes an important factor to consider in an effort to improve employee performance. Job satisfaction is a powerful motivator that can influence the relationship between emotional intelligence and performance (Chin and Yusof, 2017;Schlaegel et al, 2020). Physicians are expected to have good acceptance and emotional control over how they deal with changes by optimizing the aspects of job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…This is because employees with a high level of EI can manage selfemotions and appraise other employees' emotions (Sy et al, 2006). EI is, therefore, positively associated with job satisfaction (e.g., Jung & Yoon, 2016;Kafetsios & Zampetakis, 2008;Nauman et al, 2019;Ouyang et al, 2015;Schlaegel et al, 2020;Sy et al, 2006), although in a different context. In the present study, we hypothesize that: H7: EI exerts a positive influence on job satisfaction.…”
Section: Moderating Role Of Emotional Intelligencementioning
confidence: 99%
“… Akhter et al (2021) showed that EI and CI had a positive effect on bank employees’ JS levels. Schlaegel et al (2022) found that EI dimensions were related to JS and investigated the structure of the EI-JS and EI-job performance relationship.…”
Section: Literature Reviewmentioning
confidence: 99%